Enprostil and ranitidine in duodenal ulcer healing: double blind comparative trial. Issue 6524 (29th March 1986) - Lauritsen, K; Laursen, L S; Havelund, T; Bytzer, P; Svendsen, L B; Rask-Madsen, J
Abstract : One hundred and eighty patients with endoscopically proved duodenal ulcers were allocated at random to double blind treatment with the synthetic dehydroprostaglandin E2 enprostil 35 micrograms twice daily or ranitidine 150 mg twice daily for up to six weeks. Patients completed the study if ulcer healing and pain relief had occurred at two or four weeks. A total of 163 patients completed the trial. The duration of treatment was longer in the enprostil group (p less than 0.005) and the cumulative healing rates at two, four, and six weeks were 51%, 74%, and 85%, respectively. In the ranitidine group the corresponding figures were 65% (p less than 0.04), 89% (p less than 0.02), and 99% (p less than 0.002). More patients treated with ranitidine reported relief of pain (p less than 0.004 at weeks 5 and 6). The observed superiority of ranitidine 150 mg twice daily over enprostil 35 micrograms twice daily questions the clinical relevance of using so called "cytoprotection" as treatment for duodenal ulcer disease in the short term.